2019
DOI: 10.1080/15389588.2019.1616086
|View full text |Cite
|
Sign up to set email alerts
|

Toward harmonizing prospective effectiveness assessment for road safety: Comparing tools in standard test case simulations

Abstract: Objective: With the overall goal to harmonize prospective effectiveness assessment of active safety systems, the specific objective of this study is to identify and evaluate sources of variation in virtual precrash simulations and to suggest topics for harmonization resulting in increased comparability and thus trustworthiness of virtual simulation-based prospective effectiveness assessment. Methods: A round-robin assessment of the effectiveness of advanced driver assistance systems was performed using an arra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…For each virtual testing scenario, a baseline simulation (no driver reaction or AEB system intervention) was performed as well as a simulation with a virtual AEB system, described in Schachner et al ( 52 ). The AEB was calibrated to an individual system by using the following system parameters, which are in line with the suggestions of the Prospective Effectiveness Assessment for Road Safety (PEARS) consortium ( 53 ): Maximum sensor range in [m], Azimuth sensor opening angle [°], Azimuth sensor resolution [°], Trigger at which braking is induced – implemented based on Time to Collision (TTC) [s], Brake Delay [s] and Braking Gradient [m/s 3 ]. The parameters of the virtual AEB system were selected as described in Schachner et al ( 52 ).…”
Section: Methodsmentioning
confidence: 99%
“…For each virtual testing scenario, a baseline simulation (no driver reaction or AEB system intervention) was performed as well as a simulation with a virtual AEB system, described in Schachner et al ( 52 ). The AEB was calibrated to an individual system by using the following system parameters, which are in line with the suggestions of the Prospective Effectiveness Assessment for Road Safety (PEARS) consortium ( 53 ): Maximum sensor range in [m], Azimuth sensor opening angle [°], Azimuth sensor resolution [°], Trigger at which braking is induced – implemented based on Time to Collision (TTC) [s], Brake Delay [s] and Braking Gradient [m/s 3 ]. The parameters of the virtual AEB system were selected as described in Schachner et al ( 52 ).…”
Section: Methodsmentioning
confidence: 99%
“…All studies used some type of virtual simulation, sometimes accompanied by test-track testing. The virtual simulation setup itself can influence the evaluation of the effect (Wimmer et al, 2019), and should therefore be considered when reviewing and interpreting the results. Some studies used simulation tools that were open source or available commercially (Abdel-Aty et al, 2022;Klug et al, 2018;Paéz et al, 2015;Schachner et al, 2020;Siebke et al, 2023;Zhao et al, 2019) and details are suggested to be found in referenced documents.…”
Section: Methods and Tools For Simulationmentioning
confidence: 99%
“…In an online survey (created with Google Form (Google, 2021)), 25 experts evaluated the importance of the influence parameters collected from four sources in the first phase and their potential influence on safety effectiveness of ADAS. Invitations will be extended to experts through the networks of EVU (European Association for Accident Research and Analysis), P.E.A.R.S consortium (Wimmer et al, 2019), Virtual Vehicle Research Center, TU Graz, and TU Darmstadt. The invited experts will be required to have a minimum of 3 years of experience in the corresponding research discipline, as outlined in Table 2.…”
Section: Second Phase: Identifying the Importance Of The Influence Pa...mentioning
confidence: 99%